Characterization of Host-Guest Composite Material (SBA-15)-(p-Acetylarsenazo) - Xue, Yu; Fan, Xiao-Yu; Zhai, Qing-Zhou (Asian Journal of Chemistry, 2011)
SBA-15 molecular sieve was synthesized using tetraethylorthosilicate as silica resource in acidic medium by using triblock copolymers (EG20PG40EG20) as template. Guest material pacetylarsenazo (ASApA) was incorporated into the molecular sieve host to obtain host-guest composite material (SBA-15)-ASApA. Powder X-ray diffraction results suggested that the ordered degrees of the SBA-15 in the host-guest composite materials were still remained good and the frameworks of the molecular sieves were not destroyed by incorporation of the guest. Infrared spectra showed that frameworks of the host of prepared materials were kept intact. Low-temperature nitrogen adsorption-desorption results at 77 K showed that the surface area and the pore volume of the prepared host-guest composite materials decreased compared to those of the host molecular sieve, indicating that the guest has partially occupied channels of the molecular sieve. Scanning electron microscopic studies indicated that the composite materials (SBA-15)-ASApA presented fibrous appearance and their size was 335 ± 10 and 343 ± 10 nm, respectively. Luminous spectra showed that the prepared host-guest nanocomposite materials have the character of luminescence.